2017
DOI: 10.1111/fwb.12907
|View full text |Cite
|
Sign up to set email alerts
|

Do upstream migrating, juvenile amphidromous shrimps, provide a marine subsidy to river ecosystems?

Abstract: The upstream migration of juvenile amphidromous shrimps has been proposed as a source of marine or estuarine‐derived nutrients into fresh water. Little is known about the size and ecological importance of any such subsidy as there have been few observational or empirical studies on the topic. We investigated the upstream migration of the amphidromous shrimp, Macrobrachium spinipes (Palaemonidae) in the Daly River, of tropical northern Australia, to determine migration phenology, estimate migration biomass and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
1
7
0
Order By: Relevance
“…Furthermore, studies have shown that certain species or life history stages of shrimp have microhabitat and elevational preferences partly as a function of food and habitat rather than purely reflecting predation upon them (e.g. Fossati et al., 2002; Novak et al., 2017). It would be informative to apply both day and night visual surveys perhaps in combination with backpack electrofishing of shrimps along the predator cline in streams, to disentangle the relevance of shrimp density (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that certain species or life history stages of shrimp have microhabitat and elevational preferences partly as a function of food and habitat rather than purely reflecting predation upon them (e.g. Fossati et al., 2002; Novak et al., 2017). It would be informative to apply both day and night visual surveys perhaps in combination with backpack electrofishing of shrimps along the predator cline in streams, to disentangle the relevance of shrimp density (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…15,74 All principles reflected the strong relationships between Indigenous peoples, water, and non-human life in this catchment. For example, principle 5 promotes maintaining longitudinal connectivity of the river for fish and freshwater prawn migration 75,76 and for connecting Indigenous groups through complex cosmologies i.e., ''the songlines go right through, even to the (upper) catchment areas . the water follows the songlines.''…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotopes can also be used to help parse out the directional patterns of animal-mediated subsidies. To understand the origin of nutrients, strontium and sulphur isotopes may be used to help identify the source location of subsidies used in certain materials such as bone and cartilage (Novak et al, 2017). In certain cases, nitrogen isotopes can also be useful for identifying marine to terrestrial nutrient translocation (Hargan et al, 2017).…”
Section: Rates and Directional Patterns Of Animal Species Movement And Consequent Nutrient Transfermentioning
confidence: 99%